Innovative Approaches to Assessing Language Proficiency in Digital Learning Environments - Suryanti, Suryanti; Sok, Vann; Dara, Sokha (Journal International of Lingua and Technology, 2024)
The rapid advancement of digital technology has significantly impacted education, including language learning and assessment practices. Traditional methods of language proficiency assessment, which often rely on written tests, are no longer adequate to meet the needs of learners in digital learning environments. The emergence of digital tools and platforms provides new opportunities for more flexible, interactive, and personalized assessments that can capture a holistic picture of language proficiency. This research aims to explore innovative approaches to assessing language proficiency in digital learning environments, with a focus on integrating modern technologies such as artificial intelligence (AI) and machine learning into assessment practices. The study employs a mixed-methods approach, combining qualitative and quantitative data collection through surveys, interviews, and experimental implementation of digital assessment tools. Data is analyzed to evaluate the effectiveness of these tools in accurately assessing different dimensions of language proficiency, including speaking, listening, and writing skills. Results indicate that AI-powered assessments provide real-time feedback, promote learner engagement, and offer a more personalized learning experience. Additionally, digital environments enhance the authenticity of language tasks by simulating real-life communication scenarios. The conclusion of the study suggests that innovative digital approaches offer a more comprehensive and responsive assessment framework, aligning with the evolving needs of modern language learners. Future research should explore further refinement of these tools to ensure their accessibility and effectiveness across diverse learner populations.